Research in personnel and human resources management - Buckley, M. Ronald; Halbesleben, Jonathon R.; Wheeler, Anthony R. (Research in personnel and human resources management ;, 2016)
Volume 34 of Research in personnel and human resources management contains six chapters on emerging issues in the field of human resources management, thus continuing the tradition of the RPHRM series to publish cutting-edge work that pushes the field forward. The subject matter in this volume covers myriad areas: discrimination, multigenerational issues, duty, flexible HRM, social media, and entrepreneurship. These chapters, written by a collection of the finest scholars in the field from across the world, represent seminal scholarly advances and illustrate the interdisciplinary character of human resources management.